(untitled) (Journal of Human Sciences, 2021)
The current study aims to show a part of Libyan local history, specifically the first Italian occupation of Fezzan in 1913. It’s most important pillars and circumstances and the role of popular resistance in addressing it. This study also focuses on the most important tribal figures who fought colonialism, and follows the stages of the emergence of the idea of leadership, and leadership in the war following the signing of the O’Shea Lausanne Convention 1912. And some aspects of the leadership conflict that took place in that period between the resistance and non-resistance Supporters. As well as this paper contained in some detail in the names of the most important tribes and their leader in Fezzan and their great success in sparing the region leadership disputes over leadership such as that occurred in the western region Tripoli and Nafusa Mountains, and their success in expelling Italian colonialism from Fezzan during the period 1914 – 1924.